QCD Boltzmann equation: beyond the soft-scattering approximation - Moodley, Nicole (Department of Physics, 2023)
In this thesis we use the case study of a spatially homogeneous many-gluon system, distributed isotropically in momentum space, to study the evolution of a hot (quark-) gluon plasma from an initial state towards equilibrium. To that end, we investigate the QCD Boltzmann equation making use of a calculation scheme that reproduces the known result for scalar interactions and generalizes to a QCD interaction, under an approximation of soft scattering.